Relationship of left ventricular, elastic and muscular arteries remodeling in patients with uncontrolled arterial hypertension - S. Ya. Dotsenko; V. G. Deynega; N. Ya. Dotsenko (Zaporozhye State Medical University, 2013)
Introduction. Uncontrolled hypertension is observed in 65-92% of hypertensive patients. It plays an important role in the development of adverse cardiovascular events and survival, which depend on subclinical target organ damage. There are reports on the relationship between ineffective hypertension control and left ventricular (LV) hypertrophy or large arteries stiffness. However, the nature of the remodeling in uncontrolled hypertension remains poorly understood. Objective: to study the character and relationship of left ventricular and arterial remodeling depending on effectiveness of hypertension control. Design and method. We performed a study of 363 hypertensive patients (160 men and 203 women aged 50,8 ± 1,2 years) without comorbidities, which were divided into 3 groups according to the effectiveness of blood pressure (BP) control: 160 patients with controlled hypertension, 142 patients with uncontrolled hypertension and 61 patients with resistant hypertension. Uncontrolled BP based on measured systolic BP≥140 mmHg and diastolic BP≥90 mmHg. Remodeling indexes of left ventricular, elastic (common carotid) and muscular (brachial) artery were evaluated by the ultrasonic method. The severity and character of diastolic dysfunction, hypertrophy, types of remodeling and stiffness were assessed. Statistical processing of the results was performed using Student's t criterion and Pearson correlation analysis. Results and discussion. According to the results of the study, uncontrolled hypertension affected the development of subclinical cardiovascular lesions negatively. Thus, LV hypertrophy was detected more frequently in the third group (91,8% in resistant hypertension versus 46,8% in controlled hypertension, p<0,05). Differences in LV geometry with increasing of concentric remodeling types were also observed more frequently in the third group, where concentric remodeling and concentric hypertrophy types were founded in 14,8% and 59,0%, respectively. Subclinical arterial remodeling was founded in all groups, which was accompanied by an increasing mass of arterial segment and arterial stiffness, but most often in uncontrolled and resistant hypertension. There were unidirectional remodeling of both types of arteries and LV. LV hypertrophy had a direct relationship with the arterial mass by using correlation analysis. Violation of the geometry of both type of arteries was similar to the changes of LV geometry and was more particularly observed in the third group too (more than half of the patients with resistant hypertension had concentric types of remodeling). Thus, concentric hypertrophy of the common carotid artery was found in 42,2% of patients with concentric left ventricular hypertrophy, compared with 3,1% (p <0,05) in the group with normal left ventricular geometry. In contrast, normal left ventricular geometry was associated with normal type of geometry of the common carotid artery in 76.3% of patients, against 11,2% (p <0,05) in the group with concentric left ventricular hypertrophy. Similarly, a close correlation between diastolic dysfunction and arterial stiffness was found. Conclusion. Hence, remodeling of left ventricular, elastic and muscular arteries in uncontrolled and resistant hypertension is systemic and unidirectional. Established relationship between the severity and types of ventricular and arterial remodeling indicates a systemic effect of common pathogenic factors. Overall, these structural changes manifest increasing markers of adverse vascular events, most significantly in uncontrolled and resistant hypertension, which has the negative prognostic significance.